A Rare Case of the Small Cell Neuroendocrine Carcinoma of urinary Bladder (Anis Hussain Jafri,Aziz Abdullah, Saba Jamal) - Anis Hussain Jafri; Aziz Abdullah; Saba Jamal (Journal of Bahria University Medical and Dental College)
Small cell neuroendocrine carcinoma of urinary bladder (SCCB) is a rare, prevalent in males, highly aggressive carcinoma being diagnosed usually at advanced stages. The origin of the disease is unknown; however the multipotent stem cell theory applies best to this case. Histology and immune histochemistry shows a tumor which is indistinguishable from small cell lung carcinoma (SCLC). We report a case of SCCB in a 70 year old female who presented with history of recurrent urinary tract infections and hematuria for six months. CT scan showed a large mass in bladder, infiltrating muscle along the left lateral wall with no extra-vesical extension. Cystoscopy revealed a muscle invasive mass protruding into the bladder lumen, extending from 3-5 o’clock. Initial histopathology showed poorly differentiated urothelial neoplasm. She underwent an uneventful radical cystectomy with urinary